Effect Of Reward And Punishment On Employee Performance - Frimayasa, Agtovia; Windayanti, Windayanti; Fathiani, Fathiani; Rahmat, Rahmat; Febrian, Wenny Desty (IJOSMAS, 2021)
This study aims to determine the effect of Reward and Punishment on employee performance at PT Askrindo (Persero) Jakarta. The type of research used is quantitative. Data was collected by distributing questionnaires to 51 respondents to employees of PT Askrindo (Persero) Jakarta. The results showed that the Reward variable (X1) had a positive and significant effect on the Employee Performance variable (Y) and the Punishment variable (X2) had a positive and significant effect on the Employee Performance variable (Y) through t test (partial test) with the value of the Reward variable coefficient ( X1) is 3.201, while the t-table value is 1.685. So it can be concluded that the t-count is 3.201 > t-table 1.67722 and the significant value is 0.002, and the value of the Punishment coefficient (X2) is 1.67722, so it can be concluded that the t-count is 3.735 > t-table is 1.67722 and the significant value is 0.000. The calculation result of Adjusted R Square shows that 78% of employee performance can be influenced by Reward and Punishment.Leadership Style